SLA DEVELOPMENT ON CHILD'S PRAGMATICS DEVICES THROUGH MOM THEO’S TIKTOK - Susanto, Dias Andris (Applied Research on English Education (AREE), 2025)
This study aims to explore the development of pragmatic language in young children exposed to digital content, particularly through the TikTok platform. The primary focus of this research is on children who are bilingual in Indonesian and English, and how they adjust their language use in different social contexts. This study employs a qualitative approach with a descriptive design, involving the observation of TikTok videos and document analysis of verbal interactions on the platform. The two TikTok channels studied are Omar & Mom Official and Mom Theo, where both children, Omar and Theo, engage in bilingual communication in the context of language learning through social media. The results show that these children begin to understand and adjust their language use depending on the audience and communication situation. Their pragmatic language use demonstrates the development of the ability to adapt to broader social contexts. The exposure to digital content, which is mostly monologic, also limits their social interaction, reducing opportunities to practice pragmatic language in more dynamic contexts. Furthermore, the role of the family environment in language learning is crucial, with parents actively engaged in daily communication and supporting their children's language development. This research provides insights into how social media can influence the development of children's pragmatic language, highlighting the importance of balancing digital interactions with real-life social experiences.